IDENTIFICATION OF STRATEGIC DIRECTIONS FOR THE DEVELOPMENT OF THE E-GOVERNANCE SYSTEM IN THE CONTEXT OF INFORMATION SECURITY - KUTOVA, Maryna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article identifies strategic directions for developing Ukraine’s e-governance system, emphasizing information security aspects. The author notes that the development of information society significantly transforms traditional approaches to public administration. E-governance acts as a critical tool that ensures transparency, efficiency, and responsiveness of public administration processes. However, the adoption of advanced information and communication technologies (ICT) simultaneously generates new cybersecurity challenges. The research analyzes the existing regulatory and legal framework, institutional structure, technological dimensions, digital literacy initiatives, and international collaboration efforts, highlighting their importance in building a robust information security ecosystem. The regulatory environment requires continuous updating and flexibility due to rapid technological advances and evolving cyber threats. Institutional modernization, particularly the creation of specialized cybersecurity units like CERT-UA and cybersecurity departments within the Ministry of Digital Transformation, significantly enhances the state’s capabilities to address cyber threats effectively. Technological advancements enable rapid monitoring, threat detection, and innovative security management but also create dependencies on providers and risks related to software vulnerabilities. Digital literacy initiatives are essential for minimizing human-factor-related cyber threats, although their effectiveness demands a comprehensive and sustained educational approach. Finally, international cooperation is pivotal in sharing best practices and standards, despite challenges posed by political differences and varying state interests. The article concludes that future e-governance development in Ukraine should integrate a comprehensive, strategic approach emphasizing cybersecurity as an integral component of public administration.